ChemInform Abstract: 4‐Dimethylaminopyridine‐Catalyzed Multi‐Component One‐Pot Reactions for the Convenient Synthesis of Spiro[indoline‐3, 4′‐pyrano[2, 3‐c]pyrazole] Derivatives. Issue 27 (8th July 2014) - Feng, Jun; Ablajan, Keyume; Sali, Ahat
Abstract The title compounds can be prepared by a three‐ or four‐step one‐pot reaction, whereas the latter one gives better yields.